Mechanism of crocin I on ANIT-induced intrahepatic cholestasis by combined metabolomics and transcriptomics - Song, Dandan; Zhu, Pei; Dong, Yankai; Wang, Mengchao; Zhao, Anna; Xia, Hongdong; Chen, Yunting; Zhou, Qingguang; Xiang, Lun; Zhang, Junyi; Luo, Guangming; Luo, Yangjing (Frontiers in Pharmacology, 2023)
Background: Intrahepatic cholestasis (IC) is a disorder of bile production, secretion and excretion caused by various causes. Crocin I (CR) is effective in the treatment of IC, but its underlying mechanisms need to be further explored. We aimed to reveal the therapeutic mechanism of Crocin I for IC by combining an integrated strategy of metabolomics and transcriptomics. Methods: The hepatoprotective effect of CR against cholestasis liver injury induced by α-naphthylisothiocyanate (ANIT) was evaluated in rats. The serum biochemical indices including Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Total bile acid (TBA), Total bilirubin (TBIL), Direct bilirubin (DBIL), Tumor necrosis factor-α(TNF-α), Interleukin 6(IL-6), Interleukin 1β(IL-1β), liver oxidative stress indexes and the pathological characteristics of the liver were analyzed. In addition, we also performed the serum metabolomics study using UPLC-Q Exactive HF-X technology to investigate the effect of CR on the serum of rats with ANIT-induced IC, and screened potential biomarkers. The enrichment analysis of differential expressed genes (DEGs) was performed by transcriptomic. Finally, the regulatory targets of CR on potential biomarkers were obtained by combined analysis, and the relevant key targets were verified by western blotting. Results: CR could obviously improve serum and liver homogenate indexes and alleviated liver histological injury. Compared with ANIT group, CR group had 76 differential metabolites, 10 metabolic pathways were enriched. There were 473 DEGs significantly changed after CR treatment, most of which were enriched in retinol metabolism, calcium signaling pathway, PPAR signaling pathway, circadian rhythm, chemokine signaling pathway, arachidonic acid metabolism, bile secretion, primary bile acid biosynthesis and other pathways. By constructing the "compound-reaction-enzyme-gene" interaction network, three key-targets regulation potential biomarkers were obtained, including 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), ATP-binding cassette transporter G5(ABCG5), sulfotransferase2A1(SULT2A1) ，which were further verified by western blotting. Compared with the ANIT group, CR group significantly increased the expression of ABCG5 and SULT2A1, and the expression of HMGCR significantly decreased. Conclusion: Combined metabolomic and transcriptomic analysis show that CR has the therapeutic on IC. The mechanism is to regulate the biosynthesis of bile acids and bilirubin in the bile secretion pathway and the expression of HMGCR, ABCG5 and SULT2A1.